Design of a Modular Clamping System for Cooling Fin Applications in Solar Panels - Şengür, Serhat; Han, Mehmet Vefa; Özel, Cihan; Özel, Meral (My University, 2025)
In this study, a novel modular clamping system was proposed for attaching heat sink fins to Photovoltaic (PV) panels, differing from conventional methods, and a detailed model of this system was created together with the PV panel. This new model allowed heat sinks with different geometries and sizes used for cooling purposes to be connected to the PV panel. Pin geometry heat sink models were proposed to integrate heat sinks with different geometries into the modular system without changing the effective fin length geometry, and the detailed assembly of the designed PV panel, its working principles and advantages in terms of heat transfer were discussed.
Keywords: PV panel; Cooling; Heat sink; Modular design